The value impact of climate and non-climate environmental shareholder proposals - Berkman, Henk; Jona, Jonathan; Lodge, Joshua; Shemesh, Joshua (Journal of Corporate Finance, 2024)
We study the value impact of environmental shareholder proposals (ESPs) for Russell 3000 firms from 2006 to 2021. We distinguish between climate-dedicated ESPs and non-climate ESPs covering other environmental topics. We use two approaches to evaluate management's ability and willingness to select value-enhancing ESPs and reject value-destroying ESPs: (i) cumulative abnormal returns around the final proxy filing date and (ii) a regression discontinuity design around the voting threshold at the annual general meeting. Our results suggest that management has screening ability for ESPs, especially for climate proposals, and that investors and managers share common objectives in environmental activism.